Using NMR solvent water relaxation to investigate metalloenzyme-ligand binding interactions. - Leung, I; Flashman, E; Yeoh, K; Schofield, C; Claridge, T (2010)
This report demonstrates that solvent water relaxation measurements can be used for quantitative screening of ligand binding and for mechanistic investigations of enzymes containing paramagnetic metal centers by using conventional NMR instrumentation at high field. The method was exemplified using prolyl hydroxylase domain containing enzyme 2 (PHD2), a human enzyme involved in hypoxic sensing, with Mn(II) substituting for Fe(II) at the active site. K(D) values were determined for inhibitors that hinder access of water to the paramagnetic center. This technique is also useful for investigating the mechanism of suitable metalloenzymes, including order of ligand binding and modes of inhibition.